(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The system of criminal justice is the governmental and commercial organization network that manages offenders charged with conviction. There are several interrelationship pillars in the criminal justice system academics, law enforcement, forensic, judicial and corrective measures. Meaning of victim, victimology, victim’s rights – Indian scenario, the victim and the criminal justice system in India, victim’s position in modern perspective, victims’ status in the criminal justice system, role of judiciary in the criminal justice system, principal sectors of human rights abuses in the criminal justice system which is concluded that the potential facets of the position of the victim were ignored and the victim became the criminal law’s bad relationship. Several changes in the criminal justice system have led to a decrease in compensation as a criminal penalty.